Fabrication of Alumina-Zirconia Foam Using Foam Replication Method - Azi Rahimee, Muhammad Akif; Mat Noor, Fazimah (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Phase-stabilized zirconia (ZrO2) and aluminium oxide (Al2O3) are popular structural materials due to their high wear resistance, biocompatibility, and corrosion resistance. This thesis explores the fabrication of Alumina Zirconia foam through the foam replication method. The study investigates the effects of different compositions of alumina (Al2O3), zirconia (ZrO2), and kaolinite on the properties of alumina-zirconia composite foam. The objectives of this research are to fabricate alumina-zirconia (Al2O3+ZrO2) composite foam with open and interconnected pores, investigate the physical and mechanical properties of Al2O3+ZrO2 composite foam with different compositions of Al2O3, ZrO2, and kaolinite, and observe the microstructure of Al2O3+ZrO2 composite foam with different compositions of Al2O3, ZrO2, and kaolinite. Five different compositions (C1 to C5) were prepared and analysed. The methodology involves a series of steps including slurry mixing, PU foam dipping and squeezing, drying, sintering, and testing including microstructure analysis, density and porosity test, compression tests and followed by data analysis. Microstructure analysis was done to analyse the size and shape of pores, struts and pores distribution. The results showed that composition C2 with 22.5wt% alumina powder, 22.5wt% kaolin powder, 5 wt% zirconia powder, 2.5 wt% PEG powder, 2.5 wt% CMC powder, and 45 wt% distilled water had a strong structure with minimal shrinkage but showed significant compression strength compared to other compositions.